KAJIAN SISTEM PENYULUHAN PERTANIAN DI PROVINSI MALUKU - , RAHIMA KALIKY, Prof. Dr. Ir. Sunarru Samsi Hariadi,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to study the implementation and revitalization of agriculture extension